Modern and classical views on the problem of differentiating between fear, anxiety, and anxiousness - Eremeeva A. A. (Youth science in the modern world, 2025)
The article explores the issue of distinguishing between the concepts of fear, anxiety, and worry within the frameworks of classical and contemporary psychological perspectives. It examines the historical origins of these constructs, beginning with ancient philosophers such as Plato, Epicurus, and the Stoics and continuing with more recent theories, such as those of Sigmund Freud, Carroll Izard, and Charles Spielberger. Despite their frequent interchangeability, the article emphasizes that these concepts differ in fundamental ways. Special attention is given to the classification of anxiety, with various approaches to its understanding being considered. The conclusion draws attention to the importance of establishing clear distinctions between these terms for both theoretical and practical applications in psychology.
Keywords: дифференциация; тревожность; тревога; страх; anxiety; fear; differentiation; anxiousness; psychological theories; психологические теории